Does FOXP2 gene polymorphism affect the duration of orogastric tube use in moderate to late preterm neonates? A cross-sectional study in Indonesia - Mauliza, Mauliza; Dimiati, Herlina; Akmal, Muslim; Imran, Imran (Narra J, 2024)
Premature and low birth weight neonates often struggle with oral intake due to immaturity or respiratory distress. Forkhead box protein 2 gene (FOXP2) is predicted to influence oral feeding ability in newborns, but studies assessing the role of this gene in influencing oral feeding ability are limited. The aim of this study was to investigate the role of FOXP2 gene polymorphism, particularly single nucleotide polymorphism (SNP) rs17137124, on the duration of orogastric tube (OGT) use in moderate to late preterm neonates. A multi-center cross-sectional study was conducted in Lhokseumawe, Aceh, Indonesia, from September 2021 to August 2023, involving neonates with 32–36 weeks gestational age. The DNA samples were isolated from the saliva, amplified using polymerase chain reaction (PCR), and the FOXP2 gene was sequenced. The associations between FOXP2 gene polymorphisms and other plausible factors on the duration of OGT use were determined using Chi-squared test, Fisher’s exact test or Pearson correlation as appropriate. Preterm neonates with the CC genotype had the longest OGT use, averaging 3 days (39.1%). TT genotype preterm neonates required OGT use for 4, 5, and 6 days (each 33.3%), while CT genotype neonates predominantly required it for 4 days (41.7%). No significant association was found between FOXP2 genotypes and OGT use duration (p=0.233). Similarly, neonates with C allele required OGT use for 3 and 4 days, while those with T allele mostly required between 4 and 6 days, with no significant association (p=0.110). Analysis using dominant (p=0.109) and recessive models (p=0.481) also showed no significant associations with OGT use duration. However, the study found significant associations between delivery mode (p=0.002) and gestational age (p=0.001) with duration of OGT use in preterm neonates. This study highlights that FOXP2 polymorphisms have limited association with the duration of OGT use among preterm neonates.